The Procedure for Organizing Marketing Research in Industrial Enterprises in the Conditions of Modernization (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Advertising organization research, short- and long-term forecasting and enterprise results, organizational responsibility research, market analysis, sales opportunities and marketing research, and sales promotion procedures are considered.